Resente kleuter- en kinderbybels in Afrikaans en Engels : 'n krities-evaluerende ondersoek binne 'n literêr-semantiese raamwerk - Du Toit, Jacoba Wilhelmina (Afrikaans and Netherlandic Studies, 2017)
This research resulted from a concern for serious, authentic texts and the quality of adaptations. This brought the problematics surrounding the Bible and children's Bibles to the fore. The main concern is the integrity of the original text, and the depriving effect these adapted texts could have on very young listeners or readers. Chapter 1 is an introduction to this study. In chapter 2 the logical and magical dimensions of the word (as art) are examined. Chapter 3 is an attempt to define the Bible in literary semantic terms. Concepts under discussion are inter alia: oral tradition, genre, author, writer, double text (supratext and subtext), autobiography, reader and oeuvre. Chapter 4 defines children's Bibles in literary semantic terms and six prototypes are critically evaluated because of their claim to be called Bible. In chapter 5 these texts are discussed as children's literature. The last chapter gives an updated view of the child, including his religious needs and insights. A corrective on existing children's Bibles is proposed and motivated. Theoretical works on literary semantics, children's literature, developmental psychology and theology have been consulted. Although psychology and theology play a fairly important role in this study, the perspective remains literary semantic. ihe survey material includes all the English and Afrikaans toddler's and children's Bibles that were available in Cape Town, during the period 1992-1994. The main conclusion of this thesis is that the integrity of the original text, and that of the Author, have been violated (to different degrees). The implication is that the young listener has been deprived of a valuable meaninggiving source. Further it has been found that children's Bibles do not really have the right of existence as either Bible or children's literature. But the popularity and the real need for texts of this kind necessitates an alternative. A new approach is also suggested, namely, that the child starts hearing the pure Scripture already in utero. The practical outcome of this study proposes an alternative publication, which will soon be attempted. By the selection of Scriptures the selector will endeavour to give an overall view of the complete oeuvre in verbatim text. The aim is to publish such a text in various South African languages.